EMPLOYER BRANDING, JOB DESCRIPTIONS, AND COMPENSATION AS DETERMINANTS OF GENERATION Z’S JOB APPLICATION INTENTIONS - Syahril Sidik; Santi Dewi Nur Savitri; Agung Priyono; Awang Darmawan Putra (Journal of Management and Leadership, 2026)
This research is motivated by the shifting workforce composition increasingly dominated by Generation Z, who possess selective characteristics in choosing workplaces. In Kebayoran Lama, South Jakarta, the Generation Z population reached 84,933 people in 2024, making it a potential labor market segment. This study aims to determine the effect of Employer Branding, Job Description, and Compensation on Job Application Intention among Generation Z in Kebayoran Lama. The research employs a quantitative approach with a survey method. The sample consisted of 115 Generation Z respondents selected through accidental sampling. Data analysis used Structural Equation Model - Partial Least Square (SEM-PLS). Results show that Employer Branding has a positive and significant effect on Job Application Intention (t-statistic 11.280 > 1.96). Meanwhile, Job Description (t-statistic 1.346) and Compensation (t-statistic 0.506) have no significant effect. The R-Square value of 0.976 indicates the three variables collectively explain 97.6% of the variance in Job Application Intention. These findings indicate that Generation Z prioritizes company image and reputation over technical job aspects and financial rewards during initial job searches. Practically, companies should strengthen Employer Branding through collaborative culture and consistent communication of company values to attract Generation Z applicants.